2016
DOI: 10.1007/s12640-016-9669-6
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Postnatal Neurogenesis by Perinatal Asphyxia: Effect of D1 and D2 Dopamine Receptor Agonists

Abstract: Perinatal asphyxia (PA) is associated to delayed cell death, affecting neurocircuitries of basal ganglia and hippocampus, and long-term neuropsychiatric disabilities. Several compensatory mechanisms have been suggested to take place, including cell proliferation and neurogenesis. There is evidence that PA can increase postnatal neurogenesis in hippocampus and subventricular zone (SVZ), modulated by dopamine, by still unclear mechanisms. We have studied here the effect of selective dopamine receptor agonists on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 85 publications
0
12
0
Order By: Relevance
“…We have recently reported that PA induces sustained oxidative stress, reflected by a long-lasting increase of the oxidized glutathione (GSSG) level, and a high GSSG/GSH ratio, together with a decrease in tissue reducing capacity and catalase activity, resulting in apoptotic caspase-3-dependent cell death, mainly in the basal ganglia and hippocampus [ 7 , 19 ]. Endogenous repair mechanisms such as neurogenesis, synaptogenesis, and anti-apoptotic pathways have been suggested to be activated, but these are not always sufficient to resolve the deficit [ 5 , 13 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have recently reported that PA induces sustained oxidative stress, reflected by a long-lasting increase of the oxidized glutathione (GSSG) level, and a high GSSG/GSH ratio, together with a decrease in tissue reducing capacity and catalase activity, resulting in apoptotic caspase-3-dependent cell death, mainly in the basal ganglia and hippocampus [ 7 , 19 ]. Endogenous repair mechanisms such as neurogenesis, synaptogenesis, and anti-apoptotic pathways have been suggested to be activated, but these are not always sufficient to resolve the deficit [ 5 , 13 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The consumption of extra energy for the reestablishment of homeostasis might compete with the demands required for circuitries and synapsis consolidation [55]. Several studies using the Swedish experimental model have reported distinct alterations induced by PA such as thickening of both pre- [32] and postsynaptic densities [2429, 50]; protein misfolding, aggregation, and ubiquitination [2429]; interruption of postnatal neurogenesis [58]; reduction in neurite length and branching [59, 60]; myelination deficits [63]; and modifications in the levels of synapsin [52, 60] and neurotrophic factors [61]. Some researchers have suggested the existence of plastic changes in an attempt to counterbalance neuronal loss [29, 32, 52, 57].…”
Section: Discussionmentioning
confidence: 99%
“…In other words PA might modulate postnatal neurogenesis. Therefore dopamine agonists might have neuroprotective potential via facilitation of postnatal neurogenesis and restoration of damaged circuitries [58]. Certainly, in vitro studies revealed a selective decrease in the number, neurite length, and branching of dopamine neurons as a consequence of PA [59].…”
Section: Effects Of Experimental Perinatal Asphyxia On Synaptic Ormentioning
confidence: 99%
“…In humans, PA is a risk factor for several psychiatric disorders, including learning deficits and schizophrenia. Conversely, in rodents, PA is associated with delayed cell death, dopamine and histamine transmission deficits and behavioural impairments assessed at adulthood, affecting learning, spatial, and non-spatial memory and anxiety (Simola et al 2008 ; Morales et al 2010 ; Galeano et al 2011 , 2015 ; Flores-Balter et al 2016 ; Tapia-Bustos et al 2017 ). The idea of progressive dysfunction and “first” and successive hit sequences, triggering and perpetuating pathophysiological conditions and/or diseases, has recently been discussed (Marriott et al 2017 ; Israel et al 2017 ).…”
Section: Vulnerability To Recurrent Metabolic Insultsmentioning
confidence: 99%